2009
DOI: 10.1111/igc.0b013e3181996a78
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence Patterns and Prognostic Factors in Chinese Patients With Squamous Cell Carcinoma of the Vulva Treated With Primary Surgery

Abstract: The purpose of this study was to identify the prognostic factors for disease-free survival (DFS) and recurrence patterns in Chinese women with squamous cell carcinoma of the vulva treated with primary surgery. From 1980 through 2002, 100 patients with invasive squamous cell carcinoma of the vulva treated with primary surgery were included in this retrospective study. Survival analyses included the Kaplan-Meier method, log-rank test, and Cox proportional hazards model. The 5- and 10-year DFS rates were 66.5% an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 16 publications
1
14
0
1
Order By: Relevance
“…This study together with several previous examinations has demonstrated that differentiation grade plays an important role in the aggressiveness of a tumor and has a considerable impact on survival [9, 10, 13, 14, 17, 27]. …”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…This study together with several previous examinations has demonstrated that differentiation grade plays an important role in the aggressiveness of a tumor and has a considerable impact on survival [9, 10, 13, 14, 17, 27]. …”
Section: Discussionsupporting
confidence: 57%
“…Most of the available reports on prognostic factors in vSCC [13, 14] have included the analyses of cases treated with pelvic lymphadenectomy while it has been proven that such modality has negative influence on overall survival. Advantage of radiation to the pelvis in patients with positive inguinal lymph nodes as well as clinically suspected or fixed ulcerated groin nodes was confirmed in prospective randomized trials [22, 23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 A limited number of retrospective studies also identified other significant factors for recurrence and prognosis such as older age, tumor size, close surgical margin, stromal invasion, and adjuvant treatment. 4,13,14 To date, very limited data on the recurrence patterns and prognostic factors for survival after primary surgery T adjuvant therapy of squamous cell carcinoma of the vulva in the Turkish population exist. 15 The purpose of our study was to investigate the outcomes and evaluate the prognostic factors for recurrence and prognosis and the role of close margins in patients with squamous cell carcinoma of the vulva who were treated with primary surgery at our institution in the last 20 years.…”
mentioning
confidence: 99%
“…O principal padrão de recorrência após cirurgia primária é a recorrência local, sendo que os preditores mais importantes de mau prognóstico são idade avançada e comprometimento linfonodal (4) . Cirurgia primária sem dissecção de linfonodo está associada a menor sobrevida geral e sobrevida livre de doença, juntamente com o estadiamento avançado e profundidade da invasão estromal acima de 9,0 mm (5) .…”
Section: Introductionunclassified